Biological pretreatment improved subsequent xylan chemical solubilization - Felipuci, Jefferson Poles [UNESP]; Schmatz, Alison Andrei [UNESP]; de Angelis, Derlene Attili [UNESP]; Brienzo, Michel [UNESP] (Springer Nature, 2021)
Xylan is a polysaccharide of industrial interest and its solubilization demands a high quantity of chemicals. A combination of chemical and biological treatment was applied to solubilize xylan, reducing hydrogen peroxide charge. Coniophora puteana, Gloeophyllum trabeum, and Pleurotus ostreatus were grown on non-milled sugarcane bagasse up to four months. After microorganisms growth, the chemical solubilization of xylan was performed applying 3% and 6% (m/v) of hydrogen peroxide. Using 3% of hydrogen peroxide after the biological pretreatment resulted in 99.74% of the xylan solubilization after the fourth month to C. puteana growth, and 48.63% of the xylan solubilized after the first month to G. trabeum growth. The results demonstrated that the biological pretreatment reduced the recalcitrance of the sugarcane bagasse by changing its structure, allowing to solubilize a higher amount of xylan, and applying half of the chemical reagent contributing to process feasibility.
Keywords: Extraction yield; Microbial pretreatment; Microorganisms; Recalcitrance; White rot fungi